THE STUDY OF SOCIAL STRATIFICATION OF SOVIET SOCIETY IN THE PERIOD 1986-1991. IN VERSES BY V.R. TSOY - Mikhalchi, E.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
This article presents the study of the social strata of the Soviet society in the period from 1986 to 1991. During this period, the social structure was subjected to changes in connection with changes in the state system and the socio-economic life of society. The split of the Soviet state system, the abrupt transitions of representatives of social strata between their levels, the development of the youth subculture affected the products of creativity of various cultural figures of that period. Including social problems and instability of the state system were the context for the compositions of rock musicians and groups. In this regard, an analysis of the composition "Children of the Minutes" by the composer and musician, leader of the group "Kino" Tsoya V. R. was conducted, which reflected his views on a person, his place in society, social changes and division in the country. This composition was not published during the life of the author, but embodied the attitude of Tsoi V.R. to the social environment and changes in the country and in the person in the period of "Perestroika".